A Study of the Interaction of Bovine Hemoglobin with Synthetic Dyes Using Spectroscopic Techniques and Molecular Docking - Kamaljeet,; Bansal, Saurabh; SenGupta, Uttara (Frontiers in Chemistry, 2017)
Synthetic dyes are a very efficient class of dyes that are ingested or come into contact with the skin from numerous sources (cosmetics, textiles, leather, paper, drugs). An important component of their safety profile is the interactions that they form after they enter the body. Hemoglobin is a functionally important protein that can form multiple interactions with soluble compounds present in the blood, and hence forms an important aspect of the toxicological or safety profile of the dyes. Here we study the interaction between bovine haemoglobin and organic dyes using UV-Vis absorbance and fluorescence spectroscopy. Molecular modelling was used to visualise the binding site and partners of the dye molecules, within the hemoglobin molecule. We find that all four dyes studied form sufficiently strong interactions with haemoglobin to allow for the formation of potentially toxic interactions. Molecular modelling showed that all 4 dyes bound within the central cavity of the haemoglobin molecule. However, binding partners could not be identified as multiple binding conformations with very similar energies were possible for each dye.